(untitled) (Jurnal TEKNODIK, 2023)
Abstract is a short description of an article or scientific paper consisting four components, namely: (1) Problem and objective; (2) Method; (3) Result and Discussion; and (4) Conclusion and Suggestion. Abstract is written in two languages, that is, Indonesian and English. Besides, abstract is written in one paragraph without any footnote or citation, single space among rows. The impact of online system learning during the Covid-19 pandemic caused the discovery learning model to be less efective, resulting in a decrease on student interest learning. The addition of an interactive digital module supplement is a complementary means to maximize the online process with the discovery learning model. This study aims to: (1) determine the feasibility of an interactive digital module based on discovery learning, (2) increase student interest in learning. This research is a development research with a 4 D model which is summarized and optimized into 3 D. The research into 3 D. The research subjects were selected by purposive sampling, in class XI MIPA 2 SMA Negeri I Karanganyar. Research instruments include learning tools, observation sheets, interview guides and questionnaires. The questionnaire consisted of validation of the learning practitionerâ€™s assesment, validation of the learning practitionerâ€™s assesment, learning interest questionnaire, student needs analysis questitionnaire, and student response questionnaire of the media. Data analysis technique consisted of the qualitative descriptive and quantitative descriptive using Rasch analysis in the Winstep 3.73. The results of the research to: (1) interactive digital module is categorized as very suitable for use in learning based on the result of the assesment of the expert practitioners, learning experts, media experts, and material experts, and (2) pre-post results of the interest in learning questionnaire ere analyzed Rasch using the stacking method. The difference between the average results of the post-questionnaire and pre questionnaire shows that there is an improve in student interest learning.Â